Analysis of Leading Sectors and Components of the Expenditure Side that Affect Economic Growth in the Province of South Sulawesi - Amri, Muh Arif; Maski, Ghozali; Pangestuty, Farah Wulandari (Journal of International Conference Proceedings, 2023)
Resources typically support economic growth, but not all regions possess the same potential resources. The first objective of this study is to test and analyze the potential of leading sectors and shifting leading sectors in South Sulawesi Province. Second, to determine which expenditure-side components—household consumption, government consumption, investment, exports, and imports—influence South Sulawesi Province's economic growth. This study relies on secondary data that includes information on the Gross Regional Domestic Product of South Sulawesi Province and the same information for the entire nation from 2002 to 2021. This study makes use of the Location Quotient, Shift-Share, and Growth Ratio as analytical tools; while data panel regression is used to look at the factors that affect GRDP. Agriculture, construction, trade, and the services sector are the most important industries in South Sulawesi Province, according to the analysis's findings. While only partially the investment and household consumption variable has a significant impact on South Sulawesi's economic growth, simultaneously household consumption, government consumption, investment, exports, and imports all have a significant impact on economic growth.